Fire, Flood, Fish and the Uncertainty Paradox - Minnegal, Monica (The Australian journal of anthropology, 2008)
When the planet was created, the areas of the greatest biodiversity also happened to be the areas where mankind wants to reap the best reward of resources. It is not actually that complicated when you think about it, because where there is biodiversity happens to be where the resources are and it is where we happen to want to get them from. As it happened, the uranium was put in the middle of Kakadu and gold is in places where it is hard to get out. I think the creator of the universe decided to make things very interesting for environment ministers down the track. That is the reality… It is only a natural thing. (Senator Ian Campbell, Federal Minister for the Environment; Hansard 2006: 68–69)